REVIEW OF RASAYANA TANTRA- A UNIQUE APPROACH IN HEALING - Ragad, Shriram Shivajirao; Mehetre, Sunil Tulshiramji (International Journal of Research -GRANTHAALAYAH, 2020)
There are eight branches of Ayurveda, Rasayana chikitsa is one of them.it is also known as jara-chikitsa (anti-aging treatment) In Ayurveda there is not only reduce the symptoms of disease but also remove it from route. ‘Prvention is better than cure’ Ayurveda also prevent this life style disorder by nidan parivarjana, panchkarma,Rasayana chikitsa, following pathya-apthya. The concept of Rasayna-chikitsa as a branch has its own importance not only in the old age but need to be commenced in the early stage. The present article described whole about the Rasayana-chikitsa, epidemiology, types, methodology and its effect on the body.